(untitled) (Research, Society and Development, 2022)
Objective: To analyze indicators related to coverage and adherence to guidelines for the control of Cervical Cancer in Brazil from 2015 to 2020. Method: Ecological study, with a quantitative approach, prepared with data contained in the Cancer Information System and in the Outpatient Information System. Data from the demographic census of the Brazilian Institute of Geography and Statistics and the National Institute of Cancer were also used. Data analysis was performed by calculating the indicators in the Excel program and the results were arranged in the form of tables. Results: The ratio of cervical cytopathological exams in women aged 25 to 64 years and the female population of the same age group in the period studied showed a downward trend in all regions of the country. Regarding the proportion of cervical cytopathological exams in the target age group, it was found that the highest proportions were reached between the North and Southeast regions, and the lowest proportions in the South and Midwest regions. As for the proportion of cervical cytopathological exams without previous cytology, a pattern of decline was observed in all regions of Brazil and in the proportion of cervical cytopathological exams with a triennial periodicity, the North and Northeast regions presented the best performances. . Conclusion: The downward trends evidenced in the indicators of coverage and adherence to national guidelines may reflect an increase in the incidence, morbidity and mortality of cervical cancer.